Cellular distribution of cannabinoid‐related receptors TRPV1, PPAR‐gamma, GPR55 and GPR3 in the equine cervical dorsal root ganglia. (22nd September 2021) - Galiazzo, Giorgia; De Silva, Margherita; Giancola, Fiorella; Rinnovati, Riccardo; Peli, Angelo; Chiocchetti, Roberto
Abstract: Background: The activation of cannabinoid and cannabinoid‐related receptors by endogenous, plant‐derived or synthetic cannabinoids may exert beneficial effects on pain perception. Of the cannabinoids contained in Cannabis sativa, cannabidiol (CBD) does not produce psychotropic effects and seems to represent a molecule having great therapeutic potential. Cannabidiol acts on a great number of cannabinoid and cannabinoid‐related G‐protein‐coupled receptors and ionotropic receptors which have, to date, been understudied in veterinary medicine particularly in equine medicine. Objectives: To localise the cellular distribution of four putative cannabinoid‐related receptors in the equine cervical dorsal root ganglia (DRG). Study design: A qualitative and quantitative immunohistochemical study. Methods: The cervical (C6‐C8) DRG of six slaughtered horses were obtained from a local slaughterhouse. The tissues were fixed and processed for immunohistochemistry, and the resulting cryosections were used to investigate immunoreactivity for the following putative CBD receptors: Transient receptor potential vanilloid type 1 (TRPV1), nuclear peroxisome proliferator‐activated receptor gamma (PPARγ), and G protein‐coupled receptors 55 (GPR55) and 3 (GPR3). Results: Large percentages of neuronal cell bodies showed immunoreactivity for TRPV1 (80 ± 20%), PPARγ (100%), GPR55 (64 ± 15%) and GPR3 (63 ± 11%). The satellite glial cells (SGCs) were immunoreactive for TRPV1, PPARγ and GPR55. In addition, GPR55 immunoreactivity was expressed by DRG interneuronal macrophages. In addition, microglia cells were observed surrounding the neuron–SGC complex. Main limitations: The limited number of horses included in the study. Conclusions: Cannabinoid‐related receptors were distributed in the sensory neurons (TRPV1, PPARγ, GPR55 and GPR3), SGCs (TRPV1, PPARγ and GPR55), macrophages (GPR55) and other interneuronal cells (PPARγ and GPR55) of the equine DRG. Given the key role of DRG cellular elements and cannabinoid receptors in the pathophysiology of pain, the present findings provided an anatomical basis for additional studies aimed at exploring the therapeutic uses of non‐psychotropic cannabinoid agonists for the management of pain in horses.